Effects of free electrons and quantum confinement in ultrathin ZnO films : a comparison between undoped and Al-doped ZnO - Li, X. D. (2013)
Band gaps and exciton binding energies of undoped and Al-doped ZnO thin films were determined from optical absorption measurement based on the Elliott’s exciton absorption theory. As compared to the undoped films, the doped films exhibit a band gap expansion and a reduction in the exciton binding energies due to the free electron screening effect, which suppresses the excitonic absorption and results in a blue shift of the absorption edge. The undoped and doped films show the same quantum size dependence, i.e. both the exciton binding energies and band gap energies increase with decreasing grain size of the oxides.